Novel Route for the Construction of Chroman Ring System Using Cross-Coupling between Benzylic and Aliphatic Alcohols in the Presence of NaHSO4/SiO2 - Aoyama, Tadashi; Furukawa, Takuya; Hayakawa, Mamiko; Takido, Toshio; Kodomari, Mitsuo (Synlett, 2015)
Novel route for the construction of chromans from benzylic and aliphatic alcohols in the presence of NaHSO4/SiO2 has been developed. In this reaction, substituted olefins are formed from benzylic and aliphatic alcohols and then converted to chromans through intramolecular cyclization. Twenty novel chromans were synthesized by this simple procedure.
Keywords: chroman; tandem reaction; heterogeneous reaction; coupling reaction; solid acid